Children’s Press: A Space For Writing Skills Acquirement And Child’s Creation Encouragement - فاطمة الزهراء تنيو (International Journal of Social Communication, 2021)
Children’s press is regarded as one of the tools that reflects the new socialization approach, which is based on incenting kids to interact more and express their visions towards different situations, since the old ways of education has been let away, those ways that consider the learner negatively, not more than a mere receiver of knowledge. Actually children’s press is an opportunity to discover talents and encouraging them to go further, a revolutionary perception towards education process, that cultivates children self‐expression, and train them on journalistic reading and writing skills since childhood